ضرورة تعزيز مبدأ التوازن العقدي كأداة حمائية للمستهلك من التعسف في عقود الإذعان: دراسة مقارنة - محمد, اعمارة صوالح; نورة, جبارة (University of Eloued جامعة الوادي, 2020)
لقد تطورت المعاملات التجارية بحيث أصبح التعامل بالعقود النموذجة أمر حتميًا، وصار النموذج الواحد يستخدم لتقديم مئات الآلاف من السلع والخدمات، ومن بين هذه النماذج عقود الإذعان باعتبارها عقود نموذجية ملزمة، ونظرًا لأن أغلب عقود الاستهلاك تتَّسم بطابع الإذعان، فإن المتدخل أضحى من خلالها يفرض شروط تعسفية لمصلحته على حساب المستهلك، كطرف ضعيف في العقد بحيث لا يستطيع مناقشتها. والأصل العام في العقود أنها تبرم وفقًا لعدة مبادئ منها مبدأ سلطان الإرادة ومبدأ الحرية التعاقدية، إلا أن هذه المبادئ التقليدية بسبب التطورات الحديثة التي أفرزها واقع المعاملات التجارية، وظهور عدّة عقود أدّت إلى اختلال توازن الأداءات بين المستهلك والمتدخل، ممّا يستلزم معه تعزيز مبدأ التوازن العقدي، والبحث عن مبادئ جديدة تكفل تحقيقه ومواجهة الشروط التعسفية. Business transactions have evolved so that Modal Contracts become inevitable, the single model is used to deliver hundreds of thousands of goods and services. Among these models, the Adhesion Contracts which are treated as Binding Model Contracts. And since most Consumption Contracts are of the adhesion nature, through which the intervener impose unbearable conditions for his benefit at the expense of the consumer, as a weak party in the contract that he cannot discuss. The general principle of contracts is that they are concluded in accordance with many principles as the Autonomy of Will principle and the principle of Freedom of Contracts, however, because of the recent developments created by the reality of commercial transactions and the emergence of several contracts, these traditional principles led to imbalance of performances between the consumer and the intervener. All that necessitates the enhancement of the principle of Contracts' Equilibrium, and the search for new principles to ensure its achievement and to meet the unbearable conditions.
مجلد11،عدد1
Keywords: عقود الإذعان؛ الشروط التعسفية؛ المستهلك؛ المتدخل؛ حماية المستهلك؛ التوازن العقدي؛ المبادئ التقليدية.; Contracts of adhesion; Unbearable conditions; Consumer; Intervener; Consumer protection; Contract equilibrium; Traditional principles.